A study on the effects of exercise training on cortical excitability in athletes: a meta-analysis based on TMS measurements - Jiang, Xinhua; Li, Lei; Liu, Yang; Feng, Weiwei (Frontiers in Psychology, 2025)
ObjectiveThis study investigates the impact of exercise training on athletes’ cortical excitability, aiming to provide scientific evidence for optimizing training protocols and enhancing athletic performance.MethodFollowing PRISMA guidelines, a systematic search was conducted in databases including PubMed, Web of Science, Embase, and Cochrane Library up to May 1, 2025, including randomized controlled trials (RCTs) or quasi-experimental studies using transcranial magnetic stimulation (TMS) to assess cortical excitability in athletes. Study quality was evaluated using the Cochrane Risk of Bias tool. Meta-analysis was performed with RevMan 5.4 software, using standardized mean difference (SMD) as the effect size and a random-effects model to analyze heterogeneity. Sensitivity analysis was conducted using Stata 18.0.ResultsThe meta-analysis included 8 studies (245 participants). Results showed that exercise training significantly enhanced cortical excitability (n = 8, SMD = −1.2, 95% CI = −1.75 to −1.65, p < 0.01), with high heterogeneity (I2 = 71%). Subgroup analysis by exercise type indicated significant effects for combat sports and endurance sports (p < 0.05), but not for technical-tactical sports (p > 0.05). Subgroup analysis by training duration showed significant effects for long-, medium-, and short-term training (p < 0.05), with medium-term training exhibiting low heterogeneity (I2 = 0%). Sensitivity analysis and funnel plots confirmed robust results with low risk of publication bias.ConclusionExercise training significantly enhances athletes’ cortical excitability, particularly in combat and endurance sports and during medium-term training. Future research should further explore the specific effects of different training types and TMS metrics to reduce heterogeneity and optimize training design.Systematic review registrationThe systematic review has been registered in PROSPERO under the ID CRD420251045271. The registration details are available at: https://www.crd.york.ac.uk/PROSPERO/recorddashboard.